FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN BPJS DALAM PELAYANAN KEPERAWATAN DI RUANGAN RAWAT INAP KELAS III RSUD ROKAN HULU - Yurustin, Devina (Universitas Pahlawan, 2022)
The quality of health services can influence patient satisfaction. The factors that influence patient satisfaction are physical facilities, reliability of staff, responsiveness of staff, attention of staff, and guarantees. Various facts show that there are serious problems in the quality of health services in Indonesia. This means that there is no best quality control system that can be implemented. The aim of this research is to determine the factors related to BPJS patient satisfaction in nursing services in class III inpatient rooms at Rokan Hulu Regional Hospital. This type of research is analytical with a cross sectional design. The population in the study were all BPJS patients in Class III Inpatient Rooms at Rohul Regional Hospital, totaling an average of 171 people with a sampling technique using Purposive Sampling. Data collection tools use questionnaires and checklist sheets. The data analysis used in this research is univariate and bivariate analysis. There is a relationship between the factors of nurse reliability, nurse responsiveness and nurse attention with BPJS patient satisfaction in nursing services in class III inpatient rooms at Rohul Regional Hospital. It is hoped that the Rokan Hulu Regional Hospital will monitor and evaluate the performance of nurses and hold training to improve the Human Resources (HR) of nurses so that they can increase the competency of nurses to provide satisfaction to patients who receive nursing services.